(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Reverse zoonosis or zooanthroponosis is the transfer of pathogens from humans to animals. Although less studied than zoonotic diseases, this phenomenon poses significant risks to both animal and public health. The increasing human-animal interactions driven by urbanization, globalization, and environmental changes have exacerbated the occurrence of reverse zoonosis. This review evaluated the global impact and transmission patterns of reverse zoonosis, highlighting the anthropogenic and intrinsic factors contributing to its emergence. The study performed a systematic review and included 91 scientific articles published from 2000 to 2022, covering viral, bacterial, parasitic, fungal, and protozoal reverse zoonoses. This study indicated that viral infections, particularly respiratory viruses such as severe acute respiratory syndrome coronavirus-2 and influenza, have the highest incidence of reverse zoonosis, followed by bacterial infections like tuberculosis and methicillin-resistant Staphylococcus aureus. The United States, India, and Hong Kong are among the most reported regions for reverse zoonotic events. Major risk factors identified include environmental degradation, climate change, antimicrobial resistance, and global wildlife trade. The review underscores the need for enhanced surveillance systems, interdisciplinary collaboration, and stringent regulations on wildlife trade and animal husbandry practices to mitigate the risks associated with reverse zoonosis. Understanding the dynamics of human-animal pathogen transmission is crucial for developing not only effective but also sustainable strategies to protect animal populations as well as public health from emerging infectious diseases. J. Adv. Vet. Anim. Res., 11(3): 601–617, September 2024 http://doi.org/10.5455/javar.2024.k810